Genetic landscape of external auditory canal squamous cell carcinoma. Issue 8 (11th July 2020) - Sato, Kuniaki; Komune, Noritaka; Hongo, Takahiro; Koike, Kensuke; Niida, Atsushi; Uchi, Ryutaro; Noda, Teppei; Kogo, Ryunosuke; Matsumoto, Nozomu; Yamamoto, Hidetaka; Masuda, Muneyuki; Oda, Yoshinao; et al.
Abstract: External auditory canal squamous cell carcinoma (EACSCC) is an extremely rare and aggressive malignancy. Due to its rarity, the molecular and genetic characteristics of EACSCC have not yet been elucidated. To reveal the genetic alterations of EACSCC, we performed whole exome sequencing (WES) on 11 primary tumors, 1 relapsed tumor and 10 noncancerous tissues from 10 patients with EACSCC, including 1 with a rare case of synchronous bilateral EACSCC of both ears. WES of the primary tumor samples showed that the most frequently mutated gene is TP53 (63.6%). In addition, recurrent mutations in CDKN2A, NOTCH1, NOTCH2, FAT1 and FAT3 were detected in multiple samples. The mutational signature analysis of primary tumors indicated that the mutational processes associated with the activation of apolipoprotein B mRNA‐editing enzyme catalytic polypeptide‐like (APOBEC) deaminases are the most common in EACSCC, suggesting its similarity to SCC from other primary sites. Analysis of arm‐level copy number alterations detected notable amplification of chromosomes 3q, 5p and 8q as well as deletion of 3p across multiple samples. Focal chromosomal aberrations included amplifications of 5p15.33 ( ZDHHC11B ) and 7p14.1 ( TARP ) as well as deletion of 9p21.3 ( CDKN2A/B ). The protein expression levels of ZDHHC11B and TARP in EACSCC tissues were validated by immunohistochemistry. Moreover, WES of the primary and relapsed tumors from a case of synchronous bilateral EACSCC showed the intrapatient genetic heterogeneity of EACSCC. In summary, this study provides the first evidence for genetic alterations of EACSCC. Our findings suggest that EACSCC mostly resembles other SCC. Abstract : As the genetic characteristics of external auditory canal squamous cell carcinoma (EACSCC) are not yet elucidated due to its rarity, we performed whole exome sequencing and copy number analysis in EACSCC samples. The genetic alterations of EACSCC mostly resemble other SCC, although the novel amplified loci that harbor oncogenes were found.